IMPLEMENTATION OF E-LEARNING AS AN INTEGRAL PART OF THE EDUCATIONAL PROCESS - Havryliuk, Nataliia; Osaulchyk, Olga; Dovhan, Larysa; Bondar, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper aims to examine current tendencies in implementing e-learning as an integral part of the educational process. The relevance of e-learning as an advanced and effective technology of intensification and digitalization of teaching is proved. Theoretical research methods are used to analyze scientific, pedagogical and psychological researches on the issues of using e-learning while teaching students. Synthesis and analysis refine the conceptual apparatus of the study. Methods of induction and deduction have been used to establish links between basic concepts and their peculiarities, the research method has been applied to formulate conclusions of the study, the prognostic method has helped to substantiate innovations in the educational process with the use of e-learning. Scientific views have been analyzed regarding the definition of e-learning. A scientific approach to implementing e-learning in educational institutions has been carried out. Modern methods forms of e-learning have been identifies and their classification into person-oriented and group-oriented ones have been developed depending on the target audience and particular objectives of the class. It is resulted that blended e-learning can be considered as the most suitable and farsighted one. Within our investigation it has been concluded that e-learning is an effective and innovative educational technology that can improve the teaching process in educational institutions. It is been established that implementation of innovative e-learning methods at the foreign language classes have increased foreign language proficiency of students, let us involve all the group into active work, provided the best conditions for gaining listening and reading skills, increased motivation for learning, promoted personal development of students, made the teaching process student-centered.